1981
DOI: 10.1002/jbm.820150114
|View full text |Cite
|
Sign up to set email alerts
|

Piezoelectric ceramic implants: in vivo results

Abstract: The suitability of barium titanate (BaTiO3) ceramic for direct substitution of hard tissues was evaluated using both electrically stimulated (piezoelectric) and inactive (nonpolarized) test implants. Textured cylindrical specimens, half of them made piezoelectric by polarization in a high electric field, were implanted into the cortex of the midshaft region of the femora of dogs for various periods of time. Interfacial healing and bio-compatibility of the implant material were studied using mechanical, microra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
49
0
2

Year Published

1985
1985
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 101 publications
(58 citation statements)
references
References 6 publications
1
49
0
2
Order By: Relevance
“…In agreement with earlier work, increased ossification was found on piezoelectric films made from PLLA in a rabbit model. 50 A further study showing an improved biological response to piezoelectric materials was carried out by Feng et al 12 As with the earlier studies, 44,45 BaTiO 3 -containing ceramics were implanted in canine subjects. In this case, the piezoelectric material was in the form of a hydroxyapatite-barium titanate (HABT) composite.…”
Section: In Vivo Studiesmentioning
confidence: 98%
See 1 more Smart Citation
“…In agreement with earlier work, increased ossification was found on piezoelectric films made from PLLA in a rabbit model. 50 A further study showing an improved biological response to piezoelectric materials was carried out by Feng et al 12 As with the earlier studies, 44,45 BaTiO 3 -containing ceramics were implanted in canine subjects. In this case, the piezoelectric material was in the form of a hydroxyapatite-barium titanate (HABT) composite.…”
Section: In Vivo Studiesmentioning
confidence: 98%
“…44 The implantation method was the same as that used in the previous experiment. Subjective assessment of bone ingrowth at the bone-implant interface showed no differences between poled and unpoled samples.…”
Section: In Vivo Studiesmentioning
confidence: 99%
“…Other tests (8,18) showed that externally generated direct currents could increase the strength of fixation of intramedullary plugs of porous metals, but Park et al (14), failed to show that growth of bone was affected by polarization induced by physiologic loading. Similar negative results were reported by Schumacher et al (19) …”
mentioning
confidence: 97%
“…There is evidence that stress-generated potentials produced by piezoelectric ceramics can stimulate bone regeneration in situ. For example, barium titanate implants promoted osteogenesis in dog femurs (Park et al, 1981). Lithium sodium potassium niobate, a new generation of lead-free piezoelectric ceramics, has expanded its scope of reperaing bone defects owing to its better and more stable piezoelectricity compared with barium titanate (Saito et al, 2004).…”
Section: Introductionmentioning
confidence: 99%